The use of openCV in Traffic Surveillance System (TSS) - Zainab Nazar, Khalil Wafi; R. Badlishah, Ahmad, Dr.; Paulraj, Murugrsa Pandiyan, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.